Bringing It All Back Home: Corporate Venturing and Renewal Through Spin-ins. (November 2019) - Hunt, Richard A.; Townsend, David M.; Asgari, Elham; Lerner, Daniel A.
More often than not, corporate acquisitions are expensive and difficult, especially those transacted for the purpose of advancing the aims of corporate entrepreneurship (CE). Motivated by frequent, high-cost failures, firms are experimenting with novel organizational structures and fresh approaches to acquisition-driven CE. In this study, we examine the effectiveness of corporate spin-ins—acquisitions in which the acquired company is founded by former employees of the acquiring firm—in resolving key challenges of CE-motivated acquisitions Using a matched pairwise dataset of spin-in and non-spin-in acquisitions, we discover that spin-ins generate superior outcomes, positioning them as a high-potential facet of CE portfolios.